The effect of inoculant and sucrose addition on the silage quality of tropical forage legumes with varying ensilability - Heinritz, S.N.; Martens, S.; Ávila, P.; Hoedtke, Sandra (Elsevier, 2012)
The ensiling potential of 10 tropical forage legumes and one Brachiaria grass hybrid with dry matter (DM) ranging from 260 to 540 g/kg fresh matter (FM), and the effect of 4 treatments (Control, 20 g/kg FM sucrose, native Lactobacillus plantarum inoculant, L. plantarum +20 g/kg FM sucrose) on the fermentation quality of their silages after 92 d storage were assessed at laboratory scale. Best silage qualities were achieved with high DM Clitoria ternatea (542 g/kg FM), while worst silages resulted from Centrosema brasilianum (259 g DM/kg FM), especially without sugar addition. In general, both additives increased lactic acid production while dropping the pH (P<0.001). High acidification was also correlated with restricted NH3-N formation (14 to 68 g/kg of total N in the combined treatment). Butyric acid concentrations ranged from 0 to 18 g/kg DM except for C. brasilianum silages (30 g/kg DM in Control, 25 g/kg DM in L. plantarum only treatment). No clear effect of treatment could be observed for this parameter. The fermentability coefficient predicted quite well the silage quality for a couple of materials, but not consistently overall. As nitrate was scarce in all plant materials (<2.1 g/kg DM), some clostridial activity was probably favored. Acetic acid concentrations were very low (acetic + propionic acid 0 to 18 g/kg DM) except for Vigna unguiculata silages (22 to 53 g/kg DM). All silages were regarded as aerobically stable during the 4-d period of temperature measurement, except for the Lablab purpureus silages treated with the combined additive. Further research is needed on suitable native lactic acid bacteria strains for tropical forage silages to select the most suitable inoculants for differing forage species and conditions, for improving silage quality. Legume silages in particular can provide a valuable source of protein for improved animal production, which represents a livelihood of many smallholders in the tropical belt.